MicroRNAs profiling in malaria and arbovirus coinfection: A systematic review protocol - Andrillene Laure Deutou Wondeu; Alex Durant Nka; Aude Christelle Ka’e; Ezechiel Ngoufack Jagni Semengue; Sylvanie Masso; Pascal Fisemou; Adegoke Taiwo Mobolaji; Zeekah Marymag; Calvino Fomboh Tah; Rhoda Nsen Bughe; Akindeh Mbu Nji; Andrea Galgani; et al. (PLoS ONE, 2026)
Background Coinfections between malaria and arboviruses such as Dengue virus (DENV), chikungunya Virus (CHIKV), and Zika virus (ZIKV) represent a significant clinical and public health challenge. The molecular pathogenesis of these coinfections is complex and poorly understood. MicroRNAs (miRNAs) are key regulators of gene expression and play a crucial role in the host response to infection. A comprehensive profile of miRNAs implicated in malaria-arbovirus coinfection could provide novel insights into disease mechanisms and reveal new targets for improved management and therapeutic strategies. Methods The review will be conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search strategy will be executed in electronic databases (PubMed/MEDLINE, Scopus, Web of Science, Embase, CENTRAL, CINAHL) from January 2000 onwards, with no language restrictions. Grey literature sources will also be searched. Included study designs will comprise observational studies (cohort, case-control, cross-sectional) and clinical trials reporting primary data on miRNA expression. Two independent reviewers will screen records, extract data, and assess the risk of bias using appropriate tools (ROBINS-I, ROB-2, NIH tools). Data on study characteristics, patient demographics, confirmation of coinfection, miRNA profiling techniques, and differentially expressed miRNAs will be extracted. Given anticipated heterogeneity, a narrative synthesis will be performed. The strength of the evidence will be assessed using the GRADE approach. Conclusion This systematic review will provide comprehensive evidence on miRNA expression patterns associated with malaria-arbovirus coinfections. The findings will advance understanding of coinfection pathogenesis and identify potential biomarkers for improved diagnostics and therapeutics. It will also pioneer an exploration of cross-kingdom gene regulation by plant-derived miRNAs, establishing a foundation for future functional validation studies. Additionally, the miRNA profiles identified may provide foundations for developing novel therapeutic approaches, including nanoparticle-based delivery systems. Systematic review registration PROSPERO registration number: PROSPERO CRD42024600379.